2009
DOI: 10.1109/jssc.2009.2017005
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Hardening by Design of Asynchronous Logic for Hostile Environments

Abstract: Abstract-A wide range of emerging applications is driving the development of wireless sensor node technology towards a monolithic system-on-a-chip implementation. Of particular interest are hostile environment scenarios where radiation and thermal extremes exist. Radiation hardening by design has been recognized for over a decade as an alternative open-source circuit design approach to mitigate a spectrum of radiation effects, but has significant power and area penalties. Similarly, asynchronous logic design o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…For completeness, at the device-and layout-levels, there are other feasible RHBD techniques such as the adoption of high-K process [2], annular layout [2], [3], enclosed layout [2], and beta gain control of the parasitic bipolar transistors [2]. Although these RBHD techniques are advantageous to mitigate TID and SEL effects, they are not allowed to be implemented due to the limitations of the chosen 65nm CMOS process.…”
Section: Rhbd Library Cell Templatementioning
confidence: 99%
See 2 more Smart Citations
“…For completeness, at the device-and layout-levels, there are other feasible RHBD techniques such as the adoption of high-K process [2], annular layout [2], [3], enclosed layout [2], and beta gain control of the parasitic bipolar transistors [2]. Although these RBHD techniques are advantageous to mitigate TID and SEL effects, they are not allowed to be implemented due to the limitations of the chosen 65nm CMOS process.…”
Section: Rhbd Library Cell Templatementioning
confidence: 99%
“…This is because ICs embodied in electronics systems for said applications are subjected to various possible irradiations [1][3] which potentially jeopardize the functionality of ICs and at worst, permanent and irreparable damage to the ICs. To enhance robustness, ICs can be realized to be radiation-hardened by means of dedicated IC fabrication processes [4], design techniques [1]- [3] or a combination thereof. The dedicated IC fabrication processes employed for S&S applications are exotic in the sense that these processes are not readily available and whose cost are typically highly prohibitive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To circumvent the effects of these types of radiation, numerous Radiation Hardened by Design (RHBD) techniques have been proposed in the literature, the most common being the Triple Modular Redundancy (TMR) [7], Guarded Dual Modular Redundancy (GDMR) [8], gate sizing [9]- [12], and Glitch Filtering (GF) [13]- [15]. RHBD cell libraries have also been developed for both asynchronous and synchronous designs [16], [17]. One study demonstrated the benefits of using asynchronous bundled-data latch-based design techniques to reduce the area, delay, and power penalty associated with a RHBD cell library [17].…”
Section: Introductionmentioning
confidence: 99%
“…RHBD cell libraries have also been developed for both asynchronous and synchronous designs [16], [17]. One study demonstrated the benefits of using asynchronous bundled-data latch-based design techniques to reduce the area, delay, and power penalty associated with a RHBD cell library [17]. However, radiation-hardened libraries are cumbersome to design, typically generations behind stateof-the-art unhardened versions, and relatively expensive in terms to cell area, power consumption, and cell delay.…”
Section: Introductionmentioning
confidence: 99%